Rebuilding Japan (1952 _ 1972) Historical study (Journal of Human Sciences, 2021)
The contemporary stage began after Japan's restoration of its national sovereignty after the spring of 1952. The Japanese found themselves facing the process of rebuilding their country, and in July 1949, the United States announced its intention to implement a new scheme aimed reviving Japanese society to regain its role again in order to build its monopoly capitalist states on a solid base and on the Western style. The rise of Japan was related to the Prime Minister (Masigiro Bushida), who, was succeeded in persuading the American side to abandon their previous militancy towards Japan, and the spirit of awakening during his reign was accompanied by a determination to catch up with the West, to develop the industrial sector with the latest global technology, and the contemporary Japanese modernization experiment (the Economic miracle). During that time, Japan moved from a country that needed help during the 1950s to an enormous economic on the global level. Thus, Japan assumed its global position in the middle of the first world and industrial democracies, and ranked the second after the United States.